Chapter Диалектика Достоевского: имя Отца и спасительная сила детской жизни - ghidini, maria candida (Biblioteca di Studi Slavistici, 2023)
Dostoevsky's Dialectic: The Name of the Father and the Saving Power of Childhood. The artistic experience of Dostoevsky's novels combines two rather heterogeneous hermeneutic strategies - the analysis of the unconscious and of existential utopia. In the first case, Dostoevsky problematizes the completeness of the symbolic order of culture as such through the thematization of the figure and name of the Father. From the perspective of the second strategy, Dostoevsky creates his own utopia of a symbolic order, with the eternal substance of people's life capable of infinite renewal in the child's soul in the role of the great Other. His novels reveal what can be called the creative core of culture. The murder of Fyodor Karamazov is an archetypal event, a sacrifice of the Body of the Father for the sake of the NAME of the dead Father, it initiates a paradigmatic process in the Symbolic.